Aktivitas Antibakteri Ekstrak Etanol Bulbil Porang (Amophophallus muelleri Blume.) Terhadap Bakteri Staphylococcus aureus dan Streptococcus mutans - Sapitri, Alfi; Marbun, Eva Diansari; Arisetya, Dian; Lubis, Retnita Ernayani (Herbal Medicine Journal, 2025)
The porang is a fruit produced by the porang plant which is brownish black in color, oval in shape like a stone and the size is approximately the size of small marbles to large marbles, growing between the stems of the porang plant. This study aimed to determine the activity of the ethanol extract of the porang frog (Amorphophallus muelleri Blume) as an antibacterial against Staphylococcus aureus and Streptococcus mutans bacteria and to determine the chemical compounds contained in the porang frog (Amorphophallus muelleri Blume). Porang frog simplicia powder was extracted in 96% ethanol by maceration. Simplicia powder is screened to determine its phytochemical content. The antibacterial activity test was carried out using the Kirby Bauer method using paper discs against Staphylococcus aureus and Streptococcus mutans bacteria to determine the zone of inhibition. The simplicia results showed that the simplicia frog porang had 6.08% water content, 29.11% water soluble extract, 9.70% ethanol soluble extract, 93.51% total ash content, insoluble ash content in ethanol. acid 91.96%. Simplicia said porang contains alkaloids, flavonoids, and tannins.The ethanol extract of the porang frog (Amorphophallus muelleri Blume) has antibacterial activity against Staphylococcus aureus and Streptococcus mutans bacteria.